Aĥtâ al-Tarjamah Baina Muta’allimiy al-Lugah al-Arabiyyah Lugatan Śânawiyyatan ‘inda Tarjamati al-Jumal al-Basîţah min al-Lugah al-Arabiyyah ilâ al-Lugah al-Tâmiliyyah (Translation Errors Among the Second Language Learners of Arabic when Translating Arabic Simple Sentences to Tamil) - Abdul Majeed Mohammed Aaqil; Zunoomy Muhammadu Sainulabdeen; A.M. Razick (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2022)
أن اللغتين العربية والتاملية تنتميان إلى العائلة اللغوية المختلفة، فعملية الترجمة ليس بأمر سهل. لأنهما تتضمنان القواعد المتنوعة في بناء الجمل وتركيب العبارات. ولذا، إن دارسي اللغة العربية لغة أجنبية في جامعة جنوب شرق سريلانكا يواجهون التحديات في تحديد معاني الجمل العربية وترجمتها إلى اللغة التاملية، فيهدف هذا البحث إلى تحديد التحديات التي يواجهها دارسو اللغة العربية لغة أجنبية عند ترجمة الجمل العربية البسيطة إلى اللغة التاملية. ويعتمد الباحثون في هذا البحث على المنهج الوصفي التحليلي، كما تستخدم الأدوات الآتية لجمع المعلومات. أما الأدوات الأولية فيتناول الباحثون فيها الاستبانة، واشتملت الاستبانة فقرة فيها الجمل البسيطة لفحص مدى خبرة الطلاب فى الترجمة، وفى الاستبانة يختار الباحثون 70 طالبا وطالبة حسب العينات غير احتمالية من السنة الأولى من قسم اللغة العربية بجامعة جنوب شرق سريلانكا. وأما المعلومات الثانوية فتعتمد على الكتب والمجلات والبحوث والشبكات الإلكترونية وغيرها. والنتيجة من هذا البحث عدة أخطاء عند عملية الترجمة للطلبة وهي: الخطأ في إتيان الكلمة المناسبة إلى لغة الهدف وعدم ربط الكلمة وتغيير الزمن وعدم ذكر الفاعل والحال والترجمة بعدم اعتبار سياق اللغة الهدف واستعمال الترجمة الحرفية وأسلوب التحدث، واتيان الترجمة غير مناسبة والترجمة بغير اعتبار سياق لغة الأصل والهدف ونسخ لغة الأصل بحروف لغة الهدف، وإبدال الحرف فى اللغة التاملية. Arabic is considered to be one of the Semitic language families from global languages at the same time, Tamil is one of the classical language belongs to the Dravidian language family. Considering the families of Arabic and Tamil languages, they belong to different language families. Thus, the translation process is very difficult between them. Because they contain the various rules of sentence formation and phrase composition. Therefore, students of Arabic as a foreign language at the South Eastern University of Sri Lanka face challenges in identifying the meaning of Arabic sentences and translating them into Tamil. According to this, the research aims to identify translation errors in writing of simple sentences among Arabic language learners as a second language. This research uses descrivtive analysis methods. The primary data were collected from the questionnaire distributed among 70 male and female students from the Department of Arabic Language. Secondary data were collected from books, researches, articles, and web articles. MS Excel is used for the data analysis. This research finds that most students have sufficient knowledge of translation between Arabic and Tamil languages because they have learned Arabic in Arabic colleges for about five seven, or eight years The results concludes several errors in the translation process such as; the error in taking the appropriate word to the target language, failure to link the word according to the target language, using incorrect tense patterns, failure to mention the subject and the adverb, translation does not regard the context of the target language, the use of literal translation and speaking style, and transliterating the Arabic word in the Tamil language.